New directions in comparative law (Cheltenham, [England] Edward Elgar, 2009)
"New dynamics in comparative law" which was held at the University of Orebro in May 2007."--Preface.
Introduction / Antonina Bakardjieva Engelbrekt and Joakim Nergelius -- Legal change and economic performance : an assessment / Gianmaria Ajani -- Legal cartography and comparative law / Per Bergling -- Development assistance in the legal field : promotion of market economy v human rights / Michael Bogdan -- Can human rights be exported? On the very idea of human rights transplantability / Claudio Corradetti -- 'Cut-and-paste'? Rule of law promotion and legal transplants in war to peace transitions / Richard Zajac Sannerholm -- Ontological and epistemological complexity in comparative constitutional law / Otto Pfersmann -- European constitutional law : its notion, scope and finalities / Rainer Arnold -- Governmental accountability in autonomies : A?land islands in comparison with select autonomies in Europe and elsewhere / Markku Suksi -- Viability of constitutional/non-constitutional Comparison / Johan Lindholm -- Comparative aspects of fundamental rights in Germany and Central and Eastern Europe : the example of Ukraine / Kateryna Karpova -- Making the Principles of European Contract Law : theoretical and methodological aspects / Ole Lando -- The questionable questionnaire : reflections on comparative law method in light of the Principles of European Tort Law / Marten Schultz -- Legal services in conveyancing : a European comparison / Christoph U. Schmid -- Constitutionalization of private law / Anna Lytvynyuk -- Toward an institutional approach to comparative economic law? / Antonina Bakardjieva Engelbrekt -- Modern comparative law : the forces behind and the challenges ahead in the age of transnational harmonisation / Peter -Christian Muller-Graff.
Keywords: Comparative law -- Congresses; Conflict of laws -- Congresses; Law -- Europe -- Congresses; Globalization -- Congresses